Pengaruh Pengetahuan Keuangan, Perilaku Keuangan, dan Sikap Keuangan Terhadap Kinerja Perusahaan Asuransi - Nabila Putri Pratiwi; Dheo Rimbano; Ari Rama Junianto; Erni Susanti; Giofani Jati Nugroho; Helen Eriwati; Junizar Dwi Saputra (ManBiz: Journal of Management and Business, 2025)
This article is the result of a study that aims to see how financial knowledge, financial behavior and financial attitudes affect the performance of insurance companies. Based on the results of previous studies, the results of the study using the Systematic Literature Review (SLR) and research published in journals published in Google Scholar, where the results of the study state that: Financial knowledge affects the performance of insurance companies, financial behavior affects the performance of insurance companies and financial attitudes affect the performance of insurance companies.